WOMEN ENTREPRENEURS ON THE RISE: UNVEILING THE INTERPLAY BETWEEN GOALS-MOTIVATION, ORIENTATION AND OPPORTUNITY RECOGNITION AND PERFORMANCE - Adelia Shabrina Prameka; Rizky Firmansyah (Departemen Manajemen Fakultas Ekonomi dan Bisnis Universitas Negeri Malang, 2024)
Women entrepreneurs in Indonesia significantly contribute in national economy. Traditionally, Indonesian society has a tradition of believing that women have more responsibility for the household. This study investigates the effect of entrepreneurial orientation and entrepreneurial goals and motives on woman entrepreneur performance through opportunity recognition. Respondents in this study are 220 women entrepreneurs in from several provinces in Indonesia. This study chose the Partial Least Square-based Structural Equation (PLS-SEM) model technique to analyze the data. This study successfully confirmed the influence of entrepreneurial orientation on opportunity recognition in women entrepreneurs. However, the researcher could not show the effect of entrepreneurial goals and motives on opportunity recognition in women entrepreneurs. Furthermore, entrepreneurial orientation, entrepreneurial goals and motives, and opportunity recognition significantly influence women entrepreneur performance.